(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Poly (4-vinylpyridine) and polyaniline as highly effective base catalysts have catalyzed the three-component reaction of an appropriate aldehyde, cyanoacetic acid hydrazide and malononitrile to prepare of the corresponding N-amino-2-pyridone derivatives. These reactions occur in ethanol at reflux or under microwave heating, in the presence of the base catalysts, are inexpensive and easily obtained with consistent activity.